Entrepreneurship as empowerment : knowledge spillovers and entrepreneurial ecosystems - Ratten, Vanessa (Emerald Publishing Limited, 2020)
Entrepreneurship as Empowerment focuses on entrepreneurial theory and practice through the lens of knowledge spillovers and entrepreneurial ecosystems, enabling readers to gain a better understanding about emerging trends and developments. This edited collection widens the traditional field of entrepreneurship by discussing the way in which ecosystems facilitate the flow of knowledge, thereby creating new business opportunities globally. The current state of research on knowledge spillovers and entrepreneurial ecosystems is analysed with a view to highlighting research gaps that need further attention. Entrepreneurship as empowerment examines cultural and societal expectations and contextualises entrepreneurship across places and industries. Aimed at both academics and practitioners of entrepreneurship, Ratten uses expectancy theory to understand entrepreneurship and contributes to the burgeoning body of literature from a knowledge management and practice standpoint. Entrepreneurship as empowerment provides a unique approach to understand the cultural and social expectations that are tied into being an entrepreneur today.
Includes index.
Keywords: Entrepreneurship.; Romanies -- Economic conditions.; Business & Economics -- Entrepreneurship.; elektronické knihy; electronic books